Antioxidant and antiinflammatory properties of huauzontle (Chenopodium berlandieri subsp. nuttalliae, Chenopodiaceae) fermented by Lactiplantibacillus plantarum Lp22 - Santiago-López, Lourdes; Garcia, Hugo S.; González-Córdova, Aarón F.; Vallejo-Cordoba, Belinda; Hernandez-Mendoza, Adrián (Instituto de Ecología, A.C., 2023)
Background and Aims: Huauzontle (Chenopodium berlandieri subsp. nuttalliae) is a pseudocereal native to Mexico and is part of its culinary tradition. This pseudocereal is recognized for its high nutritional value and components that are associated with beneficial health effects. However, there is currently no literature on the impact that the fermentation process would have on its bioactive properties. Therefore, the aim of this research was to evaluate the effect of fermentation by Lactiplantibacillus plantarum Lp22 in huauzontle seeds suspended in water on their antioxidant and anti-inflammatory properties in vitro. Methods: Huauzontle seeds were suspended in water (0.3%, w/v), inoculated with L. plantarum Lp22 (1%, v/v) at 108 CFU/ml, and allowed to ferment for 24 h at 37 °C. Then, seeds were recovered by filtration, grounded and aqueous extract was obtained. The antioxidant activity of the extracts was determined by the ABTS and ORAC methods. Moreover, the inhibition of the enzymes lipoxygenase (LOX) and trypsin was evaluated and the total phenolic compounds in methanolic extract (Folin-Ciocalteu method) were also determined. Key results: The antioxidant activity represented as mM of Trolox equivalents was 812.50 and 927.50 by ABTS and 1384.32 and 3391.11 for ORAC, for unfermented and fermented huauzontle, respectively (p<0.05). The inhibition of LOX activity was 40.06% and 37.24% for unfermented and fermented huauzontle, respectively, while for trypsin it was 12.53% and 14.38% (p>0.05). Besides, total phenol content was 7.49 and 20.24 mg/ml (p<0.05), respectively. Conclusions: Our findings evidence that fermentation of huauzontle improves the antioxidant and anti-inflammatory properties, which may be associated with increased phenol content. Therefore, its consumption could enhance the antioxidant and immune system of the human organism.